2019
DOI: 10.1101/785352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved serotonergic background of experience-dependent challenge-responding in zebrafish (Danio rerio)

Abstract: Forming effective responses to threatening stimuli requires the adequate and coordinated emergence of stress-related internal states. Such ability depends on early-life experiences and, in connection, the adequate formation of neuromodulatory systems, particularly serotonergic signaling. Here, we assess the serotonergic background of experience-dependent behavioral responsiveness employing a zebrafish (Danio rerio) model. For the first time, we have characterized a period during the behavioral metamorphosis in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Increased number of riskassessment behaviors were also observed in BTBR mice, an animal model of ASD also characterized by impaired sociability and high anxiety (Chao et al, 2018). In line with the above, adult zebrafish that were subjected to social isolation during their early-life stages displayed a characteristic dark avoidance behavior that could not be interpreted as an anxiolytic response, suggesting the inability to develop stress-associated arousal state (Varga et al, 2020). Our perspective that MK-801-treated zebrafish are characterized by a heightened anxiety-state, is further reinforced by their diminished weight gain, a response that is reported in rodents and zebrafish after prolonged stress exposure (Riaz et al, 2015;Fulcher et al, 2017).…”
Section: Discussionsupporting
confidence: 56%
“…Increased number of riskassessment behaviors were also observed in BTBR mice, an animal model of ASD also characterized by impaired sociability and high anxiety (Chao et al, 2018). In line with the above, adult zebrafish that were subjected to social isolation during their early-life stages displayed a characteristic dark avoidance behavior that could not be interpreted as an anxiolytic response, suggesting the inability to develop stress-associated arousal state (Varga et al, 2020). Our perspective that MK-801-treated zebrafish are characterized by a heightened anxiety-state, is further reinforced by their diminished weight gain, a response that is reported in rodents and zebrafish after prolonged stress exposure (Riaz et al, 2015;Fulcher et al, 2017).…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, in another study, developmentally isolated fish (isolated 0-7 dpf) were observed to have significantly reduced levels of DOPAC, but not dopamine, serotonin or 5-HIAA, when compared with socialreared fish in adulthood (Shams et al, 2018). Further, Varga et al (2020) observed that social isolation of fish during a critical period of behavioural metamorphosis that occurs in the juvenile stage affects later behavioural responsiveness and serotonergic signalling in the dorsal pallium. Blockade of 5-hydroxytryptamine (5-HT) signalling was sufficient to prevent the serotonin-associated brain changes and behavioural deficits, suggesting that a serotonergic mechanism, sensitive to environmental manipulation during a specific time window, modulates context-dependent behaviours in later life.…”
Section: Social Isolationmentioning
confidence: 93%